PEMBERDAYAAN MASYARAKAT BIDANG EKONOMI MELALUI PENGEMBANGAN PARWISATA DI TARUSAN KABUPATEN PESISIR SELATAN - Titik Mai Indra (IKIP Siliwangi, 2023)
Community empowerment is an effort made to give strength to the community so that the community is empowered and independent in their daily lives. This article aims to describe community empowerment in the economic field through tourism development in Tarusan, the southern coastal district. In addition, this article also seeks to see how the economic conditions of the people in the Tarusan area of the southern coastal district as a tourist area or district are. In writing this article the author uses a literature study relating to the methods of collecting library data, reading and taking notes, and processing research materials (Zed, 2008: 3). The results of the study explain that community empowerment in the economic sector through tourism development in Tarusan, the southern coastal district, has a positive impact on the economic growth and income of the local community. With the development of tourism, the community's economy also increases because of the large number of tourists or tourists visiting this area. Therefore, the most important thing in empowerment is the participation of the local community, the role of community leaders and local, district or city governments.